Discrimination between Human Colorectal Neoplasms with a Dual-Recognitive Two-Photon Probe - Lee, Hyo Won; Lim, Chang Su; Choi, Hosam; Cho, Myoung Ki; Noh, Choong Kyun; Lee, Kiyoun; Shin, Sung Jae; Kim, Hwan Myung (Analytical Chemistry, 2019)
Colorectal cancer is a major cause of cancer-related deaths worldwide. Histologic diagnosis using biopsy samples of colorectal neoplasms is the most important step in determining the treatment methods, but these methods have limitations in accuracy and effectiveness. Herein, we report a dual-recognition two-photon probe and its application in the discrimination between human colorectal neoplasms. The probe is composed of two monosaccharides, d-glucosamine and β-d-galactopyranoside, in a fluorophore for the monitoring of both glucose uptake and β-gal hydrolysis. In vitro/cell imaging studies revealed the excellent selectivity and sensitivity of the probe for glucose transporter-mediated glucose uptake and β-gal activity. Cancer-specific uptake was monitored by increased fluorescence intensity, and additional screening of cancer cells was achieved by changes in emission ratio owing to the higher activity of β-gal. Using human colon tissues and two-photon microscopy, we found that the plot of intensity versus ratio can accurately discriminate between colorectal neoplasms in the order of cancer progression (normal, adenoma, and carcinoma).
Keywords: Cancer progression; Colorectal neoplasms; Fluorescence intensities; Galactopyranoside; Glucose transporters; Selectivity and sensitivity; Two photon microscopy; Two-photon probes